Bone deep : untangling the Betsy Faria murder case - Bosworth, Charles, Jr; Schwartz, Joel J. (Lawyer) (Citadel Press, Kensington Publishing Corp., 2022)
Describes how Russ Faria was wrongfully prosecuted and convicted for his wife's 2011 murder, despite having an alibi supported by surveillance video, receipts, and friends' testimony and that her friend, Pamela Hupp, had recently replaced him as her insurance beneficiary.